Role of extracellular environment in mechanical properties of human cardiac fibroblasts and myofibroblasts - Haasbroek, Pieter Daniël (Department of Human Biology, 2022)
Acute MI results in adverse remodelling of the myocardium, eventually leading to contractile dysfunction and chronic heart failure. Collectively, the formation of fibrotic scar tissue in the left ventricle inhibits its contractile function and leads to a cardiac output loss. Cardiac fibroblast and myofibroblast cells are integral in the remodelling of injured tissue and are the most anticipated therapeutic target for cardiac fibrosis. To date, there is no anti-fibrotic therapy, which we argue, is due to the lack of knowledge on the functionality of the cardiac fibroblast. It was hypothesised that a change in stiffness of the remodelling extracellular environment associated with fibrosis leads to a change of the mechanical properties and contractile forces of cardiac fibroblasts and myofibroblasts. Hence, this dissertation aimed to investigate the effects of extracellular stiffness on mechanical properties of cardiac fibroblasts and myofibroblasts using engineered in vitro microenvironments with tuneable physical properties. Polyethylene Glycol (PEG) hydrogels offer ideal properties to serve as an extracellular matrix (ECM) mimicking biomaterial. Different techniques of mechanical characterisation used in this study established that the elastic modulus of 20 kDa 8-arm PEG-VS hydrogel crosslinked with dithiothreitol (DTT) reagent, is directly proportional to the concentration of PEG precursor used to form the material. Rheological measurements indicated an elastic shear modulus of 500 ± 13 Pa and 2721 ± 39 Pa for PEG gels of 4% (m/v) and 10% (m/v), respectively. Specialised micro-indentation and uniaxial tensile testing found PEG gels of 7%, 10%, 14% and 18% concentration to have elastic moduli of 42.0 ± 2.8 kPa, 65.3 ±8.0 kPa, 78.2 ± 8.4 kPa, and 121.5 ± 11.9 kPa, respectively. The volumetric swelling ratio was shown to be inversely proportional to the precursor concentration. The addition of cell adhesion proteins, such as RGD peptides, resulted in a decrease in the shear modulus (G') of the hydrogel, as the peptides take up PEG arms which are potential crosslinks. This slight compromise to the structural integrity is relevant when tuning in vitro 3D extracellular environments to desired conditions. Cardiac fibroblasts (CFs) and cardiac myofibroblasts (MFs), the latter obtained through stimulation with transforming growth factor-beta 1 (TGF-β1) of CF, were cultured and embedded in 3D PEG hydrogel matrices. PEG was supplemented with RGD peptides to provide cellular adhesion points, imitating the native myocardial environment. The intracellular stiffness of the embedded cells was quantified through passive mitochondrial particle tracking. We investigated the isolated effect of soft (4% m/v) and stiff (10% m/v) matrices on the stiffness of CFs and differentiated MFs. An increase in cell stiffness with was observed with an increase in matrix stiffness from soft to stiff PEG gel, with α = 0.19-0.36 through all delay times for cells in soft matrices and α = 0.09-0.18 throughout all delay times for cells in stiff matrices (p ≤ 0.05) for both standard CFs as well as for maladaptive MFs. This direct proportionality confirms that CFs behave according to the principles of mechanotransduction, using cytoskeleton-based rigidity-sensing mechanisms between themselves and their environment, and as a consequence, their inherent stiffness is regulated by the rigidity of their environment. No considerable difference of cell fluidity was found between cell phenotypes (CF & MF) in soft matrices. In stiff matrices, MFs seemed to become somewhat stiffer across the delay times, although with no significant effect. The knowledge of the extent to which the mechanics of cardiac fibroblasts and myofibroblasts and their ECM are interrelated is essential for the understanding of pro-fibrotic mechanotransduction and ECM production to prevent, attenuate and reverse cardiac fibrosis.